Explosion severity of rice dust in a spherical system - Nur Hikmah, Semawi; Siti Zubaidah, Sulaiman; Rohaida, Che Man; Siti Kholijah, Abdul Mudalip; Zatul Iffah, Mohd Arshad; Aainaa Izyan, Nafsun (Wiley-VCH Verlag, 2023)
Rice is relatively rich in minerals, including iron, magnesium, and selenium. In the presence of a spark, rice dust suspended in air in a range of concentrations can ignite and explode. The explosion characteristics of brown, black, white, glutinous, and Bario rice were studied in a 20-L spherical vessel. Brown rice recorded the highest explosion pressure and rate of pressure rise in both dried and undried forms, while Bario rice recorded the lowest. Brown rice was more combustible and tended to develop a fast flame mechanism once ignited owing to its low moisture content and high volatility, which made its explosion more severe compared to that of black, white, glutinous, and Bario rice.